2168. Regional Variation in Community-Onset and Hospital-Identified Clostridium difficile Infection, 2017. (26th November 2018) - Van Santen, Katharina; Edwards, Jonathan R; Dantes, Raymund
Abstract: Background: U.S. regional variation in C. difficile infection (CDI) and specifically community-onset CDI (CO-CDI) is not well understood. Methods: CO-CDI was defined as a positive C. difficile stool test collected on or before hospital Day 3 (admission was Day 1), reported by acute care hospitals to the Centers for Disease Control and Prevention's National Healthcare Safety Network (NHSN) between January 1 and June 30, 2017. Hospital-onset CDI (HO-CDI) was similarly defined but with stool collection after hospital Day 3. Hospital referral regions (HRR) were previously defined by the Dartmouth Atlas of Health Care, and represent 306 U.S. tertiary healthcare markets. Standardized infection ratios (SIRs) were calculated using separate multivariable models for CO-CDI and HO-CDI, accounting for facility-level factors, and resulted in a ratio of observed to predicted infections, similar to previously established methods. SIRs were aggregated within each facility by summing the observed and predicted events across each testing location (emergency department + observation unit [ED/OBS], inpatient), then aggregated by state or HRR by summing all facility observed and predicted events within the region. Results: A total of 92, 683 CO-CDI events were reported from 4, 241 acute care hospitals. C. difficile test type, hospital size, ICU bed size, and ED/OBS reporting were independently and significantly associated with CO-CDI incidence and included in SIR models. State-level CO-CDI SIRs ranged from 0.666 to 1.456 (mean 0.961 Figure 1). Among 306 HRRs, the mean number of CO-CDI reporting facilities was 12 (interquartile range [IQR] 5–14), with a mean of 303 (IQR 101–306) CO-CDI events per HRR. HRR SIRs ranged from 0 to 2.271 (median 0.958, Figure 1). An aggregate SIR of CO-CDI and HO-CDI, representing all hospital-identified CDI similarly is shown (Figure 2). Conclusion: CO-CDI and HO-CDI reported by acute care hospitals to NHSN varied across the United States. Although adjustments were limited to only facility-level factors, aggregation of CDI SIR by HRR results in increased regional resolution of CO-CDI burden compared with state maps and may be a beneficial tool for infection preventionists and public health authorities to further understand regional CDI patterns. Disclosures: All authors: No reported disclosures.